(untitled) (Sains Humanika, 2013)
Student as a mathematics teacher candidate must have competence in solving and creating mathematical problems. This paper describes how the two competencies are mastered by students. On the one competence, problem solving ability is reviewed by using four aspects: (1) conceptual and procedural understanding, (2) strategy knowledge, (3) mathematical communication ability and (4) accuracy. On the other competence, student’s creativity in developing mathematical problem is evaluated based on: (1) fluency, (2) flexibility and (3) novelty. Research subjects are students who take Integral Calculus course in the academic year of 2012. Data are collected through documentation, observation and interview and then analyzed quantitatively and qualitatively. Students show their abilities and some difficulties in both solving and creating mathematical problem.